Association of Cyp11a Gene with Polycystic Ovarian Syndrome Patients in Lahore, Pakistan: Cyp11a Gene with Polycystic Ovarian Syndrome Patients - Rao, Attirish; Rao, Ayat Ul Jahra; Wahab, Zainab; Qudsia, Hafiza Kashaf; Javed, Rafia (Pakistan Journal of Health Sciences, 2025)
Polycystic ovary syndrome is caused by gene polymorphisms that manufacture steroid hormones, androgens and cortisol. The overexpression or downregulation of Cyp11a1 gene mutations of steroidogenesis worsens the hyper-androgenic phenomenon. However, there is a gap in the relationship between polycystic ovary syndrome, hyperandrogenism, and Cyp11a gene polymorphisms. Objectives: To investigate the association between Cyp11a gene in polycystic ovary syndrome, and to analyze the levels of di-hydro-testosterone in cases and controls. Methods: The study was conducted within six months at The University of Lahore. A sample of 75 participants (25 PCOS, 25 a-PCOS, and 25 controls was collected to test di-hydro-testosterone levels. Then 25 polycystic ovary syndrome patients and 25 control patient samples were used for PCR amplification for the Cyp11a1 gene. Results: The mean age of polycystic ovary syndrome, a-PCOS (anovulatory), and Controls were 22.68, 22.5 and 22.13, respectively. The Cyp11a1 (10:74348306 G>C) had an odds ratio of 1.199, indicating the presence of an allele in polycystic ovary syndrome and controls. Meanwhile, the odds ratio 1.179, indicated that the allele was 1.2 times more common in polycystic ovary syndrome than the controls. The polycystic ovary syndrome levels of di-hydro-testosterone were higher than the control and a-PCOS groups, with mean values of 278.18, 260.97, and 190.83, respectively. Conclusions: Cyp11a SNP rs6495096 was present in both polycystic ovary syndrome and controls, and a weak relationship exists between the Cyp11a1 gene variation and polycystic ovary syndrome. The di-hydro-testosterone levels were high in both the polycystic ovary syndrome and a-PCOS groups compared to the control group.